2022
DOI: 10.3389/fpubh.2022.814927
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure to Triclosan and Male Fecundity: A Prospective Study in China

Abstract: Triclosan (2,4,4′-trichloro-2′-hydroxy-diphenyl ether, TCS) is widely used in personal care and household products. It is ubiquitous across the ecosystem nowadays. Several in vitro and in vivo studies have suggested the possible adverse effects of TCS on male reproductive health. However, little research has been done on human beings, especially in eastern countries. To assess the effects of TCS exposure on male fecundity, we recruited couples who planned to conceive and went to the preconception care clinics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Exposure to TCS may have adverse effects in the early stages of human reproduction, and prolonged exposure may lead to decreased fertility ( Jurewicz et al, 2020 ). Research by Du et al found that TCS exposure disrupts the biosynthesis of steroid hormones and the dynamic balance of hormones, thereby affecting reproductive development ( Zhu et al, 2022 ). TCS has direct or indirect estrogenic effects, possibly by competing with estrogen receptors and disrupting steroidogenic enzymes, disrupting the synthesis of follicle-stimulating hormones, luteinizing hormones, and testosterone, thereby affecting hormone secretion and function ( Yoon and Kwack, 2021 ).…”
Section: Reproductive Toxicity Of Triclocarban and Triclosanmentioning
confidence: 99%
“…Exposure to TCS may have adverse effects in the early stages of human reproduction, and prolonged exposure may lead to decreased fertility ( Jurewicz et al, 2020 ). Research by Du et al found that TCS exposure disrupts the biosynthesis of steroid hormones and the dynamic balance of hormones, thereby affecting reproductive development ( Zhu et al, 2022 ). TCS has direct or indirect estrogenic effects, possibly by competing with estrogen receptors and disrupting steroidogenic enzymes, disrupting the synthesis of follicle-stimulating hormones, luteinizing hormones, and testosterone, thereby affecting hormone secretion and function ( Yoon and Kwack, 2021 ).…”
Section: Reproductive Toxicity Of Triclocarban and Triclosanmentioning
confidence: 99%
“…A prospective study in China including 443 couples reported that increased levels of triclosan in male urine have been linked to reduced fecundity (OR 0.77; 95% CI, 0.62–0.97). Furthermore, there was a notable rise in the risk of infertility, indicated by an odds ratio (OR) of 1.6 (95% CI, 1–2.6) ( 129 ).…”
Section: Physiological Effects Of Edcs On Male Infertilitymentioning
confidence: 99%
“…DHEP and BPA are currently found in urine of men and they negatively impact sperm quality (sperm count, morphology and motility) (82). While genetic factors certainly play a crucial role in semen quality decline, environmental factors, including exposure to EDCs like triclosan (found in antibacterial soaps, toothpaste, hand sanitizers, and even some cosmetics), have been hypothesized to disrupt the endocrine system and potentially affect the development and function of the male reproductive system (129). A prospective study in China including 443 couples reported that increased levels of triclosan in male urine have been linked to reduced fecundity (OR 0.77; 95% CI, 0.62-0.97).…”
Section: Spermatogenesismentioning
confidence: 99%